Three-dimensional imaging of microstructures by an improved compact digital holographic microscope (ICDHM) with dual wavelength - Wen, Yongfu (2018)
An improved compact digital holographic microscope (ICDHM) is developed for three-dimensional imaging of microstructures. This system is based on lensless magnification using a diverging wave. A point source generated by a long working distance microscope objective is located into the cube beam-splitter to get a higher numerical aperture (NA) of the system. The lateral resolution and the field-of-view of the system are confirmed with a calibration experiment. For the case of the optical path lengths (OPL) of object with step pattern larger than the wavelength, the traditional phase unwrapping algorithms cannot be unequivocally determinate, resulting in a 2π phase ambiguity. To solve this problem, dual wavelength phase unwrapping method was integrated into ICDHM, which extends the measuring capability of ICDHM over several microns of range. The experimental results demonstrate that the developed system is well suitable for the measurement of MEMS and Micro systems samples with high resolution.